Impact of heat-assisted HVED plasma treatment on quality of apple juice - Vukušić, Tomislava (Array, 2020)
High voltage electrical discharge (HVED) plasma processing receives more and more attention due to its potential to assure microbial safety and retain quality of treated products. The influence of combined thermal and high voltage electrical discharge plasma treatment on apple juice quality was investigated. Apple juice samples were treated under defined plasma treatment parameters of time (3, 6 and 9 min), frequency (60, 90 and 120 Hz) and temperature (30, 40 and 50 oC) in hybrid plasma reactor. Prior to treatment, juice samples were inoculated with Saccharomyces cerevisiae ATCC 204508 to investigate inactivation possibilities of plasma treatment on yeasts as common juice microorganisms. Quality parameters (pH, electrical conductivity, phenolic content and antioxidant activity) of treated and untreated apple juice were investigated and compared. Results have shown effectiveness of HVED plasma treatment in yeast inactivation up to 6.6 log10 in 9 min of treatment at 120 Hz and temperature of 40 oC. In treated samples there were no significant changes in phenolic content.